Microbiological profile of isolated microorganisms from patients in intensive care units of a Hospital in Lambayeque, Peru, 2019-2020 - Marco A. Chilon-Chavez; Jery G. Muñoz-Inga; Heber Silva-Díaz (Revista de la Facultad de Medicina Humana, 2022)
Objective: To describe the microbiological profile of microorganisms isolated from patients in critical care units of a hospital in the Lambayeque region in 2019-2020. Materials and methods: Descriptive, retrospective, cross-sectional study with a quantitative approach. A census study was carried out on 332 patients from critical care units with a positive microbiological culture registered in the file of the microbiology laboratory of the Lambayeque Regional Hospital in 2019-2020. The statistical software Info stat v8 was used for statistical analysis. Results: The median age was 50 years, predominantly male (55.1%). The most frequent culture sample was bronchial secretion (35.8%). The most frequently isolated microorganisms were A. baumannii complex (27.7%) resistant to meropenem and imipenem with 90.7% and 89.3% respectively, P. aeruginosa (13.9%) resistant to cefepime with 55.8% and 61.1% for Piperacillin / tazobactam, E. coli (11.1%) resistant to ampicillin with 94.7%; and K. pneumoniae (9.9%) resistant to ampicillin / sulbactam by 79.2%. Conclusion: The most frequent microorganisms isolated from the study population were the A. baumannii complex, P. aeruginosa, E. coli and K. pneumoniae; isolated mainly from respiratory secretions, of which the first two showed high resistance to carbapenems and aminoglycosides, and in the next two, half were ESBL.